The Challenges of University Graduates in The Labour Market During The Industrial Revolution 4.0 Era - Manuntun Parulian Hutagaol; Bomer Pasaribu; Nurmala Katrina Pandjaitan; Ami Pujiawati (LPPM Universitas Terbuka, 2022)
Purpose - This study aims to determine the relevance of the competencies acquired by university graduates in the labor market during the industrial revolution 4.0 era. This is necessary considering the fact that the evolution of this industrial era has triggered the creation of new types of works which require inexperienced college graduates to improve their competencies. Methodology - Data were obtained from Faculty of Economics 2015-2019 alumni at Universitas Terbuka domiciling on Java Island. A total of 279 alumni were used as samples while the data was collected using a questionnaire and analyzed through Biplot. Findings - The results showed that the graduates surveyed fulfilled several competencies required in the labor market but need to improve on some others such as digital, technological, and humanist literacies observed to be needed in industrial revolution era 4.0. Novelty - This study highlights some of the competencies possessed by graduates to operate in the labor market era 4.0 and several others to be improved in order to compete globally.